Analysis of current and future technologies of capsule endoscopy: A mini review - Alexander P Brown; Ahalapitiya H Jayatissa (Archives of Preventive Medicine - Peertechz Publications, 2020)
Many existing methods of endoscopy can be very uncomfortable and potentially even painful for a patient. Using a conventional endoscope is also limited in its usable range, unable to access a majority of the small bowel. Recent advancements in LEDs, optical design, and MEMS (microelectromechanical systems) technologies have provided the ability to create a wireless endoscope. Since its inception, the capsule endoscope has seen advancements in existing technology as well as the introduction of new components. As the capsule endoscope continues to advance, more application possibilities will grow as well.